2021
DOI: 10.1186/s40851-021-00175-x
|View full text |Cite
|
Sign up to set email alerts
|

The digestive tract as an essential organ for water acquisition in marine teleosts: lessons from euryhaline eels

Abstract: Adaptation to a hypertonic marine environment is one of the major topics in animal physiology research. Marine teleosts lose water osmotically from the gills and compensate for this loss by drinking surrounding seawater and absorbing water from the intestine. This situation is in contrast to that in mammals, which experience a net osmotic loss of water after drinking seawater. Water absorption in fishes is made possible by (1) removal of monovalent ions (desalinization) by the esophagus, (2) removal of divalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 276 publications
(485 reference statements)
0
17
0
Order By: Relevance
“…The intestine is an essential organ for conditioning fish osmotic pressure during this process. It can efficiently exchange fluids to compensate for dehydration caused by hyperosmotic environments (Takei, 2021 ), which host various microorganisms having complex community structures. During long-term evolution, gut microbes have formed interdependent and mutually constrained relationships with their host's chronotype, influencing the host's susceptibility to infection by exogenous pathogens (Abid et al, 2013 ; Cahenzli et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intestine is an essential organ for conditioning fish osmotic pressure during this process. It can efficiently exchange fluids to compensate for dehydration caused by hyperosmotic environments (Takei, 2021 ), which host various microorganisms having complex community structures. During long-term evolution, gut microbes have formed interdependent and mutually constrained relationships with their host's chronotype, influencing the host's susceptibility to infection by exogenous pathogens (Abid et al, 2013 ; Cahenzli et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Haemolymph osmolarity measured in O. vulgaris, O. insularis and O. ocellatus ranged from ~940 to ~1170 mOsm/kg (Amado et al, 2015;Sakamoto et al, 2015) so is slightly hypo-osmotic or iso-osmotic with sea water. The values are comparable to marine osmoconforming fish but considerably higher than the osmoregulating teleosts (Takei, 2021). Wells and Wells (1989;1993) investigated water uptake in O. vulgaris and concluded that the digestive gland appendage ("pancreas") is one site of fluid and ion transport.…”
Section: Introductionmentioning
confidence: 91%
“…Sea water drinking occurs in marine teleosts and elasmobranchs and is an important component of fluid and ionic homeostasis (for review see: Grosell, 2010;Takei, 2021). Haemolymph osmolarity measured in O. vulgaris, O. insularis and O. ocellatus ranged from ~940 to ~1170 mOsm/kg (Amado et al, 2015;Sakamoto et al, 2015) so is slightly hypo-osmotic or iso-osmotic with sea water.…”
Section: Introductionmentioning
confidence: 99%
“…Consumed SW is desalinated within the esophagus to yield a fluid that is closer to the osmolality of plasma (Hirano & Mayer‐Gostan, 1976). It is currently thought that Na + and Cl − are removed from the lumenal fluid and transported into the blood via Na + /K + ‐ATPase (Nka), Na + /H + exchangers (Nhes), Cl − /HCO 3 − exchangers, and ClC‐family Cl − channels (Esbaugh & Grosell, 2014; Takei, 2021; Takei et al, 2017), though this is based on limited study of only a few euryhaline species. The absorbed Na + and Cl − is subsequently secreted by branchial ionocytes (Kaneko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%